HUBUNGAN OLAHRAGA DENGAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE II - Marlin Sutrisna; Hanifah Hanifah; Neni Triana; Fatimah Nuraini Sasmita (KOLONI, 2022)
The number of diabetes mellitus patients in 2045 is predicted to reach 629 million cases. This study aims to determine the relationship between exercise and blood sugar levels in patients with Type II diabetes mellitus. The method used is a descriptive research design with a cross sectional approach. The population in this study were all patients with diabetes mellitus (Type II) in the Work Area of the Betungan Health Center. The number of samples in this study were 32 respondents. Sampling technique with accidental sampling. This study uses the chi-square test. The results of the univariate test analysis found that most of the respondents (59.4%) with irregular exercise in Type II diabetes mellitus patients, most of the respondents (53.1%) and most of the respondents (59.4%) with blood sugar levels abnormal. While the bivariate analysis test found that there was a relationship between exercise and blood sugar levels in Type II diabetes mellitus patients with p-value = 0.011 and 0.010 (p-value ≤ 0.05). Keywords: Diabetes Mellitus Type II, Blood Sugar Levels, Exercise